EKSISTENSI GURU PAI SEBAGAI KONSELOR DALAM MENGATASI MASALAH BELAJAR - Fathiyyah Putri Pasaribu; Cipto Halomoan Ritonga; Hidayani Syam (CV. ADIBA AISHA AMIRA, 2025)
Student problems are obstacles experienced by students in their eflorts to study each subject studied at school or things that can result in failure in their learning progress. Teachers play an important role in helping students overcome learning problems, improving student achievement and learning outcomes as a reference for teachers in teaching so that they can become better materials for students in facing and overcoming student learning problems, and for schools contributing important information that is good for schools in order to improve teaching and learning process of Islamic Religious Education. How to overcome The results of this article show that: (1) Choose the right PAI learning method, so that students do not get bored and fed up with PAI subjects, especially reading and memorizing the Al-Qur'an. (2) Use of varied media, whether sourced from print, electronic media and so on, to support the learning process. (3) Always provide motivation to students after completing learning activities and strengthen the enthusiasm in their souls so that the students are happy with the teacher and their brains become receptive to lessons.